2004
DOI: 10.1089/cap.2004.14.481
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome in an Adolescent After Brief Exposure to Olanzapine

Abstract: A 17-year-old African-American male developed neuroleptic malignant syndrome (NMS) with hyperthermia, autonomic instability, increased muscle tone, rhabdomyolysis, and obtundation after a maximum of 2 days of treatment with olanzapine and 1 day of treatment with divalproex sodium. Intensive care unit (ICU)-level care was required. Paranoid psychosis with catatonia was present after recovery from the NMS. Because of his continued psychotic symptoms following resolution of the NMS, the alternate atypical antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There may be other explanations with respect to risperidone-induced increases in REE and TEE. The activity of skeletal muscle may contribute to the increased energy expenditure, as AAD treatment results in increased muscle tone in patients (29) and rats (30). Moreover, the automatic nervous system is deeply involved in the regulation of energy metabolism, and one study indicated that AADs induce instability in the automatic nervous system (31), which may increase firing rates of sympathetic nerves leading to increased energy expenditure (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…There may be other explanations with respect to risperidone-induced increases in REE and TEE. The activity of skeletal muscle may contribute to the increased energy expenditure, as AAD treatment results in increased muscle tone in patients (29) and rats (30). Moreover, the automatic nervous system is deeply involved in the regulation of energy metabolism, and one study indicated that AADs induce instability in the automatic nervous system (31), which may increase firing rates of sympathetic nerves leading to increased energy expenditure (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis of NMS includes serotonin syndrome, malignant hyperthermia (secondary to halothane or succinylcholine), and drug-induced hyperthermia (cocaine, phencyclidine, methylenedioxymethamphetamine) (Hanft et al 2004;Zimmerman et al 2006). NMS may occur in up to 1% of all patients on neuroleptic agents with incidence rates ranging from 0.02% to 3% (Bourgeois et al 2002;Levenson 1985).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,27 While there have been case reports of the atypical antipsychotics clozapine, risperidone, aripiprazole, ziprasidone, and olanzapine successfully treating catatonia, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] these agents have also been reported to cause catatonia. [43][44][45][46][47][48][49][50] In fact, Rosebush and Mazurek noted that the failure to treat catatonia before institution of antipsychotic medication may increase the risk of inducing neuroleptic malignant syndrome. 51 In some benzodiazepine-resistant cases, N-methyl-D-aspartate (NMDA) receptor antagonists, including amantadine (initial dose 100 mg three times a day, up to 500 mg three times a day reported) and memantine (initial dose 5 mg/day, up to 20 mg/day reported) may provide benefit.…”
Section: Introductionmentioning
confidence: 99%